2020
DOI: 10.37335/ijek.v8i2.116
|View full text |Cite
|
Sign up to set email alerts
|

Successful Management System by a Metalworking Mexican Company During Covid-19 Situation. Analysis Through a New Index (Case Study).

Abstract: The implications of the COVID-19 pandemic have jeopardized many corporations around the globe, especially those that were centered around what is considered to be a non-essential activity. The objective of this research is to discover what strategies the company in question applied successfully within its diverse areas, leading its system management to an overall positive outcome, despite having to adapt to 7 months of COVID-19. In order to achieve this, the company's data will be examined before the pandemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…However, Moore, Kissinger [ 68 ]; Sierra, Flores [ 69 ]; Wackernagel and Rees [ 61 ] suggest that proper management in the physical infrastructure and transportation sector can benefit economic growth. They suggested that vehicle mileage taxes provide direct and indirect benefits at many scales, such as reducing pollution, improving air quality, promoting public safety and health, and reducing fossil fuel consumption and increasing employment in public transportation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, Moore, Kissinger [ 68 ]; Sierra, Flores [ 69 ]; Wackernagel and Rees [ 61 ] suggest that proper management in the physical infrastructure and transportation sector can benefit economic growth. They suggested that vehicle mileage taxes provide direct and indirect benefits at many scales, such as reducing pollution, improving air quality, promoting public safety and health, and reducing fossil fuel consumption and increasing employment in public transportation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The activity of many corporations worldwide has been jeopardised due to Covid-19 implications. Sierra et al (2020) discuss successfully implemented strategies in a metal working Mexican company, by computing a new index of organisational prevalence. Sawangchai et al (2020) use an e-questionnaire on entrepreneurial Thai university students and prove that the quality of e-services and e-information positively influence e-learning education for entrepreneurs in the context of Covid-19 (Wach & Bilan, 2021;Nowiński et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The family environment highly affects university students' interest in doing entrepreneurship. Self-concept allows recognizing the environment easier and faster and spot business opportunities better (Carrasco Sierra et al, 2020).…”
Section: Literature Beckgroundmentioning
confidence: 99%